Viral piracy of host RNA phosphatase DUSP11 by avipoxviruses. - Kayla H Szymanik; Emily A Rex; Vamshikrishna R Pothireddy; Don B Gammon; Dustin C Hancks; Christopher S Sullivan (PLoS Pathogens)
Proper recognition of viral pathogens is an essential part of the innate immune response. A common viral replicative intermediate and chemical signal that cells use to identify pathogens is the presence of a triphosphorylated 5' end (5'ppp) RNA, which activates the cytosolic RNA sensor RIG-I and initiates downstream antiviral signaling. While 5'pppRNA generated by viral RNA-dependent RNA polymerases (RdRps) can be a potent activator of the immune response, endogenous RNA polymerase III (RNAPIII) transcripts can retain the 5'ppp generated during transcription and induce a RIG-I-mediated immune response. We have previously shown that host RNA triphosphatase dual-specificity phosphatase 11 (DUSP11) can act on both host and viral RNAs, altering their levels and reducing their ability to induce RIG-I activation. Our previous work explored how experimentally altered DUSP11 activity can impact immune activation, prompting further exploration into natural contexts of altered DUSP11 activity. Here, we have identified viral DUSP11 homologs (vDUSP11s) present in some avipoxviruses. Consistent with the known functions of host DUSP11, we have shown that expression of vDUSP11s: 1) reduces levels of endogenous RNAPIII transcripts, 2) reduces a cell's sensitivity to 5'pppRNA-mediated immune activation, and 3) restores virus infection defects seen in the absence of DUSP11. Our results identify a context where DUSP11 activity has been co-opted by viruses to alter RNA metabolism and influence the outcome of infection.